Persepsi Siswa Terhadap Pembelajaran Kelas Secara Luring dengan Adaptasi Kebiasaan Baru di Era New Normal - Sartinem (Pencerah Publishing, 2021)
Adaptation of new habits is a policy implemented by the government to mark a new phase in the New Normal era which is marked by re-opening of schools again for areas other than the red zone. Aceh Province as one of the regions that has succeeded in getting out of the red zone carries out offline classroom learning. Offline classroom learning is learning that requires students and teachers to attend class and learn directly while still applying adaptations to new habits such as wearing masks, keeping distance, and washing hands or using hand sanitizers while in the school environment. The method used is a quantitative method, namely by measuring students' perceptions of offline classroom learning by implementing new habit adaptations. Respondents in this study were students of class VI Elementary School 1 Alue Bilie, totaling 51 students. The data were obtained by distributing questionnaires which were then analyzed using a Likert scale. The conclusion of this study shows that students' perceptions of offline classroom learning with the adaptation of new habits are positive with a value of 84%. That is, from a total of 51 students who became respondents strongly agreed with the holding of offline classroom learning (face-to-face) with the adaptation of new habits such as wearing masks, maintaining distance, and always washing hands while in the school environment. The reason is because it is easier to understand the material in class, can ask and answer subject matter directly, besides that students also enjoy the process of working on assignments given in class directly with the teacher.